A critical analysis of oppositional discourses of the ideal female body in women's conversations - Pienaar, Kiran Merle (Rhodes University, Faculty of Humanities, Department of English Language and Linguistics, 2007)
Socialisation agents such as the popular media and same age female peers construct and reproduce notions of what is physically ideal, feminine and beautiful in a woman (Hesse-Biber 1996). My interest lies in how a group of young women reproduce, contest and possibly transform such notions in conversations with their same age female friends. The study aims to answer the following question: What ideologies are reflected and perpetuated in the discourses associated with the ideal female body? Since notions of what is ideal and beautiful are indeterminate and in perpetual flux, I focus in particular on areas of contradiction and contestation in the body talk conversations. As such, the analysis examines three extracts in which the young women draw on oppositional discourses to construct notions of female beauty. I believe that these extracts represent discursive struggles in relation to the dominant Western ideal of the slim, toned female body, an ideal which more closely resembles a newly pubescent girl's body than the curvaceous, shapely body of an adult woman (Bartky 2003; Grogan 1998). My analysis is based on conversational data collected from sixteen, white adolescent English-speaking women between the ages of fourteen and eighteen who attend a boarding school in Grahamstown. I elicited the body talk data using three stimulus exercises designed to encourage discussion on topics such as the overweight female body, dieting and the ideal body. I selected three extracts from the recorded conversations and used the methodological framework of Critical Discourse Analysis to analyse the data. This framework proposes three interdependent stages of analysis: 1) the Description of the formal features of the text, 2) the Interpretation of the text in terms of the participants' background assumptions, the situational context and the intertextual context and 3) an Explanation of the text in light of the sociocultural context and the text's contribution to the reproduction or transformation of the status quo. Since I was present during the conversational recordings and contributed to the discussions, part of the interpretation stage of analysis critically evaluates how the asymmetrical power relations between myself and the participants influenced the conversations. In this regard, my findings attest to my coercive role in promoting conservative, reactionary discourses which sustain the dominance of traditional ideologies of female beauty and which stifle oppositional ideologies. My interpretation of the extracts also reveals that, in their discussions of topics such as excess weight, female ageing and cosmetic surgery, the young women negotiate alternative conceptions of what constitutes the ideal female body. However, the articulation of an alternative beauty ideal, one which values women of different body sizes and ages is not sustained in the extracts. By discussing the relationship between these alternative constructions and dominant norms of beauty, I show how the prevailing ideal of the youthful, slim, toned female body wins out in the conversations. The interpretation of the extracts also reveals the participants' preoccupation with the pursuit of health and wellÂ¬being. In this respect, the young women construct the ideal body as not only slim and youthful, but also healthy. In my explanation of the extracts, I explore the sociocultural factors which have contributed to the rise of the health ethic. In concluding, I argue that the valorisation of the healthy body in the conversations, far from challenging the imperative to be thin, actually reinforces it by constructing dieting as a necessary adjunct to the pursuit of health. From this perspective, the preoccupation with attaining the ideal thin, toned body can be justified in terms of a desire to be healthy.
Keywords: Conversation analysis; Women in mass media; Self-perception in women; Self-perception in adolescence; Body image